Process parameter optimization and performance comparison of AISI 430 and AISI 1018 in resistance spot welding process. (2020) - Ravichandran, P.; Anbu, C.; Meenakshipriya, B.; Sathiyavathi, S.
Abstract: Resistance spot welding (RSW) process plays an important role in the sheet metal fabrication process, in which metal joining is obtained by heat developed through electric resistance against the current flow in the metals contact area. In this work, the impact of weld time, squeeze time, weld current and hold time on weld strength of 1.2 mm thickness ferritic stainless steel (AISI 430) and low carbon mild steel (AISI 1018) sheets by using RSW process were investigated and compared. The Design of experiment (DoE) was used to formulate the number of experiments with variations in input conditions. Welding of similar metals of AISI 430 and AISI 1018 was done according to the number of experiments obtained using DoE. The welded samples were subjected to tensile shear failure load and micro-hardness testing. The output responses were analyzed through Response surface methodology (RSM) to find the optimum control parameters to achieve higher weld strength.